Analisis Penggunaan Antibiotik pada Pasien Sepsis Neonatus di RSUD Arifin Ahmad Provinsi Riau - Nazardi Oyong; Inayah Inayah; Yuni Novita; Rizki Giofani (Jurnal Ilmu Kedokteran, 2017)
Sepsis that is commonly caused by bacterial infection may cause death in neonates. The appropiate antibioticadministered will increase the life expectancy of neonates with sepsis. Objective of this study was to know the patternof antibiotic use and appropriateness of antibiotic use based on sensitivity test. The study used observational methodwith cross sectional design. The collected data were retrospective. The study population were neonates with sepsis inperinatal ward from Januari – December 2014. The criteria of inclusion were positive blood culture with sensitivity testsand use of antibiotics. The percentage of particular antibiotics used in neonates with sepsis before sensitivity testwere amikacin 64,3%; meropenem 62,9% and piperazine/tazobactam 50% with suitability of 27,1%. However, aftersensitivity test there were meropenem 38,6%, amikacin 30%, vancomycin 14,3% and piperaciline/tazobactam 14,3%with appropriateness of 64,3%. The most number of antibiotic used before and after sensitivity test were amikacin andmeropenem, respectively. There was a suitability enhancement between the use of antibiotics and sensitivity testresults.